2015
DOI: 10.1007/s11010-015-2531-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel adipokine C1q/TNF-related protein 3 is expressed in developing skeletal muscle and controls myoblast proliferation and differentiation

Abstract: Several hormones and growth factors, including adipokines, play important roles during muscle development and regeneration. CTRP3, a paralog of adiponectin, is a member of the C1q and tumor necrosis factor-related protein (CTRP) superfamily. CTRP3 is a novel adipokine previously reported to reduce glucose output in hepatocytes and lower glucose levels in mice models. In the present study, we provide the first evidence for a physiological role of the CTRP3 in myogenesis using C2C12 myoblasts. CTRP3 was expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…While, the top 3 genes induced in miR106b-93-25 −/− ischemic-muscle (compared to WT) CXCL2 (50,51) , IRG1 (34,52) and GM3893 were intimately associated with immune responses (with the exception of GM3893, a long non-coding RNA) the top 3 downregulated genes C1QTNF3 (53) , MYH3 (54,55) and ACTC1 (56,57) were closely associated with skeletal muscle function. These data clearly indicated an inverse correlation between genes that regulate immune cell function and skeletal muscle perfusion-recovery in miR106b-93-25 −/− ischemic-muscle.…”
Section: Discussionmentioning
confidence: 99%
“…While, the top 3 genes induced in miR106b-93-25 −/− ischemic-muscle (compared to WT) CXCL2 (50,51) , IRG1 (34,52) and GM3893 were intimately associated with immune responses (with the exception of GM3893, a long non-coding RNA) the top 3 downregulated genes C1QTNF3 (53) , MYH3 (54,55) and ACTC1 (56,57) were closely associated with skeletal muscle function. These data clearly indicated an inverse correlation between genes that regulate immune cell function and skeletal muscle perfusion-recovery in miR106b-93-25 −/− ischemic-muscle.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot of evidence to indicate that ERK1/2 pathway is involved in regulating the proliferation of muscle cells272829. To gain insight into the mechanisms by which Akirin2 stimulates the proliferation and differentiation of porcine skeletal muscle satellite cells, we evaluated the signaling events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the effect of MAPK on muscle cells differentiation is controversial. Some studies suggest that activation of the ERK pathway prevents skeletal muscle differentiation293031, and other studies believe that it functions at two stages of skeletal muscle differentiation1032. However, recent data indicate that ERK1/2 may positively regulate myogenic differentiation62833.…”
Section: Discussionmentioning
confidence: 99%
“…Among the CTRPs, CTRP3, also known as CORS26/cartducin, was first identified as a growth plate cartilage-derived secretory protein (Maeda et al, 2001). It has also been reported to be expressed in myotubes (Otani et al, 2015), adipocytes (Sch€ affler et al, 2003), and adipose tissues (Wong et al, 2008). Several studies using animal models have revealed that CTRP3 administration decreases blood glucose levels and suppresses hepatic gluconeogenic gene expression in normal and insulin-resistant ob/ob mice (Peterson et al, 2010), and that it reduces hepatic triglyceride levels in dietinduced obese (DIO) mice .…”
Section: Introductionmentioning
confidence: 99%